Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematik Mahasiswa Pendidikan IPA - Azrina Purba; Riskyka Riskyka (Keguruan, 2022)
This research aims to  know the effect of the problem based learning model on students’ ability of mathematical problem solving of second semester Science education study program students of STKIP Al Maksum Langkat 2021/2022 academic year on the subject of basic mathematics. This research is a quasi-experimental research. The population of this study were all second semester students of Science Education Study Program of STKIP Al Maksum Langkat of 2021/2022 of academic year. Two from the three classes  were selected as research samples.  The purposive sampling technique was carried out in this study. The test of mathematical problem solving was used as the instrument to collect the data. The Technique of data analysis was using the data prerequisite test. The finding showed that there was a significant effect of the problem based learning model on students' mathematical problem solving abilities. This finding was based on the hypothesis  t-test or independent sample test at a significant level (α) = 0.05. Based on the results of data analysis from the research, it was obtained that the average score of the  students’ mathematical problem solving ability who were taught by the problem based learning model increased better than those given conventional learning, where the increasing score of those given the treatment by using problem based learning model was 10.1333 while the increasing average score of the control class was 3.0667. The hypothesis testing was conducted in this study to know whether there was a significant effect of the problem-based learning model on students’ ability of mathematical problem solving. The results were obtained that the value of significant level (α) = 0.05, was 0.000 0.05, which means that Ha was accepted and H0 was rejected. Therefore, it can be stated that there was a significant effect of the Problem Based Learning model on students' mathematical problem solving abilities in the suject of basic mathematics.